The Role Of Company Size In Moderating The Cash Position Relationship, Return On Assets, And Debt To Equity Ratio To Dividend Payout Ratio (A Case Study on Manufacturing Companies on the Indonesia Stock Exchange in 2015-2019) - Devi Noviandari; Dimas Angga Negoro (Penerbit Kemala Indonesia, 2021)
Dividend policy is the most important decision for the company due to it is not only an income source for investors but also reflects the company's performance. In making the dividend payment policy, the company estimates the financial ratios that can influence the dividend payment policy. This study aims to determine the effect of cash position, debt to equity ratio, and return on assets on the dividend payout ratio with company size as a moderating variable. The manufacturing industry is one of the fastest-growing sectors in Indonesia, which can be seen from the number of manufacturing companies listed on the Indonesia Stock Exchange (IDX). From period to period, manufacturing companies are the most common compared to other companies. The manufacturing industry sector is fairly stable and is one of the sectors that play an important role in the Indonesian economy. There are differences in several previous studies that discuss the model and the use of company size as a moderating variable, however, not much similar study has been done. Thus, it becomes the hold of this research. This study used a quantitative approach. The sampling technique in this study used Judgment Sampling with certain considerations. 20 companies are collected from the total number of companies in the manufacturing sector. Furthermore, the data analysis technique in this study used STATA. The results of this study indicated that cash position and return on assets have a positive effect on the dividend payout ratio, while the debt to equity ratio has a negative effect on the dividend payout ratio. The size of the company is able to strengthen the effect of cash position and return on assets on the dividend payout ratio, however, the size of the company is not able to moderate the debt to equity ratio on the dividend payout ratio.